Fruit Maturity Indices As Criteria For Optimization Of Seed Germination In Jatropha Curcas L. (Applied Biological Research, 2014)
The seeds of Jatropha curcas were harvested from three maturity stages  termed as greenish-yellow (40-45 days after anthesis, DAA), yellow (55- 60 DAA) and brownish-black (65-70 DAA) at fortnightly interval from  July to December to assess the effects of collection time and capsule  maturity on seed germination. It was observed that seed germination  varied significantly with the advancement of collection period and  capsule maturity. Maximum germination was recorded in the seeds  extracted from yellow capsules both under laboratory (85.8%) and  nursery conditions (59.1%). Similarly, the seeds harvested during July,  August and September collectionsshowed higher germination percentage.  Therefore, harvesting of fruits at yellow stage during rainy season appearsbetterfor thecollection of abundantsuperiorquality seeds.
Keywords: Germination; Jatropha curcas; maturity indices